Production of knowledge on climate change perception: actors, approaches, and dimensions - Zorn, Anika; Schäfer, Susann; Tzschabran, Sophie (Geographica Helvetica, 2023)
Research on perceptions of climate change impacts contributes to understanding motivations for adaptation action and increases the legitimacy of climate adaptation research and policy. The body of literature on climate change perception (CCP) is extensive. Given that the perception of climate change is commonly presented as being dependent on an individual's sociocultural and spatial contexts and that climate change is an abstract concept with different dimensions of meaning, this paper systematizes the research in an actor-centered manner. Using a systematic literature review, the abstracts from 821 interdisciplinary studies on CCP were coded and statistically analyzed. The results show that predominantly knowledge about the CCP of vulnerable groups of actors and regions was generated using quantitative methods. Impacts at the collective and institutional levels of CCP were rarely explored. This indicates an individualizing perspective of research on climate adaptation of vulnerable actors. Conclusions for future research are drawn.
Gesehen am 27.01.2025